Donor and Acceptor Unit Sequences Influence Material Performance in Benzo[1, 2‐b:4, 5‐b′]dithiophene–6, 7‐Difluoroquinoxaline Small Molecule Donors for BHJ Solar Cells. (22nd August 2016) - Wang, Kai; Liang, Ru‐Ze; Wolf, Jannic; Saleem, Qasim; Babics, Maxime; Wucher, Philipp; Abdelsamie, Maged; Amassian, Aram; Hansen, Michael Ryan; Beaujuge, Pierre M.
Abstract : Well‐defined small molecule (SM) donors can be used as alternatives to π‐conjugated polymers in bulk‐heterojunction (BHJ) solar cells with fullerene acceptors (e.g., PC61 /71 BM). Taking advantage of their synthetic tunability, combinations of various donor and acceptor motifs can lead to a wide range of optical, electronic, and self‐assembling properties that, in turn, may impact material performance in BHJ solar cells. In this report, it is shown that changing the sequence of donor and acceptor units along the π ‐extended backbone of benzo[1, 2‐ b :4, 5‐ b ′]dithiophene–6, 7‐difluoroquinoxaline SM donors critically impacts (i) molecular packing, (ii) propensity to order and preferential aggregate orientations in thin‐films, and (iii) charge transport in BHJ solar cells. In these systems (SM1‐3 ), it is found that 6, 7‐difluoroquinoxaline ([2F]Q) motifs directly appended to the central benzo[1, 2‐ b :4, 5‐ b ′]dithiophene (BDT) unit yield a lower‐bandgap analogue (SM1 ) with favorable molecular packing and aggregation patterns in thin films, and optimized BHJ solar cell efficiencies of ≈6.6%. 1 H‐ 1 H DQ‐SQ NMR analyses indicate thatSM1 and its counterpart with [2F]Q motifs substituted as end‐groupSM3 possess distinct self‐assembly patterns, correlating with the significant charge transport and BHJ device efficiency differences observed for the two analogous SM donors (avg. 6.3% vs 2.0%, respectively). Abstract : Changing the sequence of donor and acceptor units along the π‐extended backbone of benzo[1, 2‐ b :4, 5‐ b ′]dithiophene–6, 7‐difluoroquinoxaline small molecule (SM) donors critically impacts (i) molecular packing, (ii) propensity to order and preferential aggregate orientations in thin‐films, and (iii) charge transport in bulk‐heterojunction (BHJ) solar cells. The lower‐bandgap analogue (SM1) achieves distinct local packing and aggregation patterns in thin films, and optimized BHJ solar cell efficiencies of ≈6.6%.